Al and LiH co-doped silicon negative electrode material and preparation method and application thereof

By forming co-doping of metal aluminum and lithium hydride in the silicon negative electrode material and adopting a two-step vacuum heat treatment method, the problem of poor cycling stability of silicon negative electrode material in lithium-ion batteries is solved, achieving higher first-time Coulomb efficiency and cycling stability, as well as higher electronic conductivity and battery capacity.

CN119858922AActive Publication Date: 2025-04-22ZHEJIANG BAIMA LAKE LABORATORY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510345633.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The silicon negative electrode material in lithium-ion batteries has poor cycle stability and serious dynamics, which affects battery performance due to significant volume changes and adverse interface reactions.

Method used

By forming co-doping of metal aluminum and lithium hydride in the silicon negative electrode material, a two-step vacuum heat treatment method is used to generate nano-size, high dispersion uniformity metal aluminum and lithium hydride in situ, improving the first-time Coulomb efficiency and cycling stability of lithium-ion batteries.

Benefits of technology

It improves the first Coulomb efficiency and cycle stability of lithium-ion batteries, and enhances electronic conductivity and improves battery capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119858922A_ABST
    Figure CN119858922A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery electrode materials, and discloses an Al and LiH co-doped silicon negative electrode material and a preparation method and application thereof. The preparation method comprises the following steps: carrying out powder tabletting on Si and LiAlH4, carrying out vacuum heat treatment at 160-190 DEG C for 3-6 hours, and then carrying out vacuum heat treatment at 200-300 DEG C for 2-5 hours to obtain the Al and LiH co-doped silicon negative electrode material. According to the invention, co-doping of metal aluminum and lithium hydride is formed in the silicon negative electrode material through a specific method, so that the lithium ion battery can be endowed with higher initial coulombic efficiency and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery electrode materials, and in particular to an Al and LiH co-doped silicon negative electrode material and a preparation method and application thereof. Background Art

[0002] Silicon anode materials are regarded as one of the most promising anode materials in lithium-ion batteries due to their abundant natural resources in the earth's crust, low redox voltage and high theoretical specific capacity. However, the main challenges faced by silicon anodes during electrochemical cycling include significant volume changes and unfavorable interfacial reactions, which seriously weaken the cycle stability of the battery. At the same time, the low electronic conductivity of silicon further aggravates the kinetic barriers of the electrode reaction, limits the efficient transmission of lithium ions, and thus affects the overall performance of the battery. These problems constitute the main obstacles to the commercial application of silicon anode materials in rechargeable lithium-ion batteries.

[0003] To overcome the above problems, common strategies currently include the use of silicon nanoparticles with porous structures, surface coating technology, functional electrolytes or conductive additives, and the design of new binders, aiming to enhance the cycle stability of electrode materials. Despite this, due to the significant volume change of silicon during the charging and discharging process, the single use of silicon still faces many challenges. Patent CN116404131A discloses a silicon-carbon negative electrode material with a nano-homogeneous structure and its preparation method and application. It uses white carbon black, lithium aluminum hydride and hard carbon materials as raw materials, sintering, and then coating, roasting, crushing and shaping with soft carbon materials to obtain a silicon-carbon negative electrode material in which nano-silicon and a lithium aluminate film wrapped on the surface of the nano-silicon are uniformly distributed inside the hard carbon matrix, and there is a soft carbon coating layer on the surface of the hard carbon matrix. The patent uses the doping of lithium aluminate in the silicon-carbon negative electrode material to improve the first coulomb efficiency and cycle stability of the battery to a certain extent, but the effect is limited. Summary of the invention

[0004] In order to solve the technical problem of poor first coulombic efficiency and cycle stability of batteries using silicon negative electrode materials, the present invention provides an Al and LiH co-doped silicon negative electrode material and its preparation method and application. The present invention forms metal aluminum and lithium hydride co-doping in silicon negative electrode materials by a specific method, which can give lithium-ion batteries higher first coulombic efficiency and cycle stability.

[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention discloses a method for preparing an Al and LiH co-doped silicon negative electrode material, comprising the following steps: 4 After the powder is pressed into tablets, it is subjected to vacuum heat treatment at 160-190°C for 3-6 hours and then to vacuum heat treatment at 200-300°C for 2-5 hours to obtain Al and LiH co-doped silicon negative electrode material.

[0006] The present invention adopts a two-step vacuum heat treatment method to make LiAlH 4 Decomposition according to a specific reaction path: During vacuum heat treatment at 160~190℃, LiAlH 4 Decomposed into Li 3 AlH 6 , Al and H 2 During vacuum heat treatment at 200~300℃, Li 3 AlH 6 Further decomposed into LiH, Al and H 2 ; The thermal decomposition of LiH requires a temperature of more than 400°C, so during the preparation process of the negative electrode material of the present invention, LiH does not undergo further decomposition. Through the above method, nano-sized, highly dispersed metal aluminum and lithium hydride can be generated in situ, which are doped in the silicon negative electrode material and can play the following roles: (1) The alloying / de-alloying potentials of aluminum and silicon are similar, both 0.3~0.4V (vs Li + / Li). The in-situ generated nano-aluminum particles have high reversibility of alloying / de-alloying reactions, which can improve the coulombic efficiency and cycle capacity retention rate of charge and discharge cycles.

[0007] (2) During the charging process of lithium-ion batteries, lithium ions migrate from the positive electrode to the negative electrode, and react with Si and Al in the negative electrode to form lithium-silicon alloy and lithium-aluminum alloy. 4 Through a specific two-step vacuum heat treatment method, the in-situ generated lithium hydride has the characteristics of nanometer size and high dispersion uniformity. After the nucleation of the above two alloys, the electric field effect between lithium hydride and lithium aluminum alloy and lithium silicon alloy can promote the lithium ion transmission inside the negative electrode and balance the electric field on the surface of the alloy material, thereby avoiding the growth of lithium dendrites induced by the local potential on the surface of the material, thereby improving the cycle stability of lithium-ion batteries. On the contrary, lithium hydride with large particle size and low dispersion uniformity will increase the local potential difference at each point on the surface of the alloy material, leading to the accelerated growth of lithium dendrites.

[0008] Preferably, the Si and LiAlH 4 The molar ratio is 2~8:1.

[0009] When Si and LiAlH 4 When the ratio of LiAlH is controlled within the above range, the battery capacity and cycle stability can be effectively improved; 4 When the dosage is too low, LiAlH 4 On the contrary, the use of it will lead to a decrease in battery capacity and cycle stability.

[0010] Preferably, during the vacuum heat treatment at 160-190° C. and the vacuum heat treatment at 200-300° C., the degree of vacuum is not less than 10 kPa.

[0011] Preferably, Si and LiAlH 4 Mixing and high energy ball milling were performed.

[0012] By Si and LiAlH 4 High-energy ball milling can refine the particle size of the material, which helps to make the metallic aluminum and lithium hydride generated in situ after vacuum heat treatment have smaller particle size and higher dispersion uniformity, thereby improving the first coulombic efficiency and cycle stability of lithium-ion batteries.

[0013] Preferably, the mixing and high-energy ball milling processes are carried out in an inert atmosphere.

[0014] Furthermore, the inert atmosphere is an argon atmosphere.

[0015] Preferably, the high energy ball milling method is planetary ball milling.

[0016] Preferably, during the high-energy ball milling process, the ball-to-material ratio is 60-120:1, the revolution speed is 200-500 rpm, and the time is 1-5 hours.

[0017] Furthermore, during the high-energy ball milling process, the ball-to-material ratio is 80-100:1, the revolution speed is 300-400 rpm, and the time is 2-3 hours.

[0018] Preferably, during the powder tableting process, the pressure is 100-300 MPa.

[0019] Furthermore, during the powder tableting process, the pressure is 150-250 MPa.

[0020] In a second aspect, the present invention discloses an Al and LiH co-doped silicon negative electrode material prepared by the preparation method.

[0021] In a third aspect, the present invention discloses the application of the Al and LiH co-doped silicon negative electrode material in a lithium ion battery. The lithium ion battery comprises a negative electrode; the negative electrode adopts the Al and LiH co-doped silicon negative electrode material.

[0022] Preferably, the lithium-ion battery is a solid-state lithium-ion battery.

[0023] Preferably, the lithium-ion battery further comprises a positive electrode; the positive electrode is made of a lithium-containing positive electrode material; the lithium-containing positive electrode material comprises LiNi 0.8 Co 0.1 Mn 0.1 O2 and / or LiCoO 2 .

[0024] Compared with the prior art, the present invention has the following advantages: The present invention uses LiAlH 4 The present invention uses Al and LiH as raw materials, and after a specific two-step vacuum heat treatment, nano-sized metal aluminum and lithium hydride with high dispersion uniformity are generated in situ. The obtained Al and LiH co-doped silicon negative electrode material, when used in a lithium ion battery, can enable the battery to have a higher first coulomb efficiency and cycle stability; in addition, the Al and LiH co-doped silicon negative electrode material prepared by the method of the present invention also has a higher electronic conductivity and can improve the battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The discharge specific capacity of the batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 2 varies with the number of cycles. Figure 1 In the figure, "Si" represents the battery prepared in Comparative Example 1, "Si-Al (18:1) " represents the battery prepared in Comparative Example 2, "Si-Al (8:1) " indicates the battery prepared in Example 1, "Si-Al (4:1) " indicates the battery prepared in Example 2, "Si-Al (2:1) ” indicates the battery prepared in Example 3.

[0026] Figure 2 The X-ray diffraction patterns of the negative electrode materials prepared in Example 1, Example 3 and Comparative Example 2 are shown. Figure 2 In “Si-Al (2:1) " indicates the battery prepared in Example 3, "Si-Al (8:1) " indicates the battery prepared in Example 1, "Si-Al (18:1) ” represents the battery prepared in Comparative Example 2.

[0027] Figure 3 This is a scanning electron microscope image of the negative electrode material prepared in Example 1.

[0028] Figure 4 is the electronic conductivity of the negative electrode materials prepared in Example 1 and Comparative Example 1. Figure 4 In the table, "Si" represents the negative electrode material prepared in Comparative Example 1, "Si-Al (8:1) ” represents the negative electrode material prepared in Example 1. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the embodiments.

[0030] First, the present invention relates to a method for preparing an Al and LiH co-doped silicon negative electrode material, comprising the following steps: 4 After the powder is pressed into tablets, it is subjected to vacuum heat treatment at 160-190°C for 3-6 hours and then to vacuum heat treatment at 200-300°C for 2-5 hours to obtain Al and LiH co-doped silicon negative electrode material.

[0031] In some specific embodiments, the Si and LiAlH 4 The molar ratio is 2~8:1.

[0032] In some embodiments, Si and LiAlH are firstly mixed before powder tableting. 4 Mixing and high-energy ball milling are performed. Optionally or preferably, the mixing and high-energy ball milling are performed in an inert atmosphere, which is an argon atmosphere; the high-energy ball milling is performed by planetary ball milling, with a ball-to-material ratio of 60-120:1, an orbital speed of 200-500 rpm, and a time of 1-5 hours.

[0033] In some specific embodiments, during the powder tableting process, the pressure is 100-300 MPa.

[0034] In some specific embodiments, during the vacuum heat treatment at 160-190° C. and the vacuum heat treatment at 200-300° C., the vacuum degree is not less than 10 kPa.

[0035] Second, the present invention relates to an Al and LiH co-doped silicon negative electrode material prepared by the above preparation method.

[0036] Thirdly, the present invention relates to the application of the above Al and LiH co-doped silicon negative electrode material in a lithium ion battery, wherein the lithium ion battery comprises a negative electrode; the negative electrode adopts the Al and LiH co-doped silicon negative electrode material.

[0037] In some embodiments, the lithium ion battery is a solid-state lithium ion battery.

[0038] In some specific embodiments, the lithium-ion battery further comprises a positive electrode; the positive electrode is made of a lithium-containing positive electrode material; the lithium-containing positive electrode material comprises LiNi 0.8 Co 0.1 Mn 0.1 O 2 and / or LiCoO 2 .

[0039] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.

[0040] Example 1 The Al and LiH co-doped silicon anode material was prepared and used in solid-state lithium-ion batteries by the following steps: S1: In an argon atmosphere, Si and LiAlH 4 The powder was preliminarily ground in a mortar to ensure that the two were evenly mixed to obtain Si / LiAlH 4 Mixed powder; S2: Si / LiAlH 4 The mixed powder was placed in a stainless steel ball mill, sealed, and mixed by planetary high-energy ball milling in an argon atmosphere. The ball-to-material ratio was set to 100:1, and the revolution speed of the ball mill was set to 400 rpm. The ball milling was performed for 2 h to obtain Si / LiAlH 4 Mixing ball-milled powders; S3: Si / LiAlH 4 The mixed ball-milled powder was pressed into powder tablets under a pressure of 150 MPa to obtain Si / LiAlH 4 Mixing and tableting; S4: Si / LiAlH 4 The mixed pressed tablets were placed in a stainless steel tube, and the stainless steel tube was evacuated with the help of a vacuum diaphragm valve to ensure that the vacuum degree of the environment in the tube was not less than 10 kPa during the subsequent heat treatment. The temperature in the tube was raised to 180 ° C. After heat treatment at 180 ° C for 3 hours, the temperature was raised to 210 ° C. After heat treatment at 210 ° C for 5 hours, it was then cooled to room temperature to obtain Al and LiH co-doped silicon negative electrode material, and its morphology is as follows: Figure 3 As shown; S5: Using the negative electrode material prepared in step S4 as the negative electrode, NCM811 / VGCF / Li 6 PS 5 Cl (mass ratio of 65:5:35) as the composite positive electrode, Li 6 PS 5 Cl is a solid electrolyte, and a solid-state lithium-ion battery with a laminated structure is obtained by cold pressing of powder.

[0041] Example 2 The Al and LiH co-doped silicon anode material was prepared and used in solid-state lithium-ion batteries by the following steps: S1: In an argon atmosphere, Si and LiAlH 4 The powder was preliminarily ground in a mortar to ensure that the two were evenly mixed to obtain Si / LiAlH 4 Mixed powder; S2: Si / LiAlH 4 The mixed powder was placed in a stainless steel ball mill, sealed, and mixed by planetary high-energy ball milling in an argon atmosphere. The ball-to-material ratio was set to 100:1, and the revolution speed of the ball mill was set to 400 rpm. The ball milling was performed for 2 h to obtain Si / LiAlH 4 Mixing ball-milled powders; S3: Si / LiAlH 4 The mixed ball-milled powder was pressed into powder tablets under a pressure of 150 MPa to obtain Si / LiAlH 4 Mixing and tableting; S4: Si / LiAlH 4 The mixed pressed tablets are placed in a stainless steel tube, and the stainless steel tube is evacuated with the help of a vacuum diaphragm valve to ensure that the vacuum degree of the environment in the tube is not less than 10 kPa during the subsequent heat treatment. The temperature in the tube is raised to 180° C., and after heat treatment at 180° C. for 3 hours, the temperature is raised to 210° C., and the heat treatment is continued at 210° C. for 5 hours, and then cooled to room temperature to obtain Al and LiH co-doped silicon negative electrode material; S5: Using the negative electrode material prepared in step S4 as the negative electrode, NCM811 / VGCF / Li 6 PS 5 Cl (mass ratio of 65:5:35) as the composite positive electrode, Li 6 PS 5 Cl is a solid electrolyte, and a solid-state lithium-ion battery with a laminated structure is obtained by cold pressing of powder.

[0042] Example 3 The Al and LiH co-doped silicon anode material was prepared and used in solid-state lithium-ion batteries by the following steps: S1: In an argon atmosphere, Si and LiAlH 4 The powder was preliminarily ground in a mortar to ensure that the two were evenly mixed to obtain Si / LiAlH 4 Mixed powder; S2: Si / LiAlH 4 The mixed powder was placed in a stainless steel ball mill, sealed, and mixed by planetary high-energy ball milling in an argon atmosphere. The ball-to-material ratio was set to 100:1, and the revolution speed of the ball mill was set to 400 rpm. The ball milling was performed for 2 h to obtain Si / LiAlH 4 Mixing ball-milled powders; S3: Si / LiAlH 4 The mixed ball-milled powder was pressed into powder tablets under a pressure of 150 MPa to obtain Si / LiAlH 4 Mixing and tableting; S4: Si / LiAlH 4 The mixed pressed tablets are placed in a stainless steel tube, and the stainless steel tube is evacuated with the help of a vacuum diaphragm valve to ensure that the vacuum degree of the environment in the tube is not less than 10 kPa during the subsequent heat treatment. The temperature in the tube is raised to 180° C., and after heat treatment at 180° C. for 3 hours, the temperature is raised to 210° C., and the heat treatment is continued at 210° C. for 5 hours, and then cooled to room temperature to obtain Al and LiH co-doped silicon negative electrode material; S5: Using the negative electrode material prepared in step S4 as the negative electrode, NCM811 / VGCF / Li 6 PS 5 Cl (mass ratio of 65:5:35) as the composite positive electrode, Li 6 PS 5 Cl is a solid electrolyte, and a solid-state lithium-ion battery with a laminated structure is obtained by cold pressing of powder.

[0043] Example 4 The Al and LiH co-doped silicon anode material was prepared and used in solid-state lithium-ion batteries by the following steps: S1: In an argon atmosphere, Si and LiAlH 4 The powder was preliminarily ground in a mortar to ensure that the two were evenly mixed to obtain Si / LiAlH 4 Mixed powder; S2: Si / LiAlH 4 The mixed powder was placed in a stainless steel ball mill, sealed, and mixed by planetary high-energy ball milling in an argon atmosphere. The ball-to-material ratio was set to 100:1, and the revolution speed of the ball mill was set to 400 rpm. The ball milling was performed for 2 h to obtain Si / LiAlH 4 Mixing ball-milled powders; S3: Si / LiAlH 4 The mixed ball-milled powder was pressed into powder tablets under a pressure of 150 MPa to obtain Si / LiAlH 4 Mixing and tableting; S4: Si / LiAlH 4 The mixed pressed tablets are placed in a stainless steel tube, and the stainless steel tube is evacuated with the help of a vacuum diaphragm valve to ensure that the vacuum degree of the environment in the tube is not less than 10 kPa during the subsequent heat treatment. The temperature in the tube is raised to 160° C., and after heat treatment at 160° C. for 6 hours, the temperature is raised to 300° C., and the heat treatment is continued at 300° C. for 2 hours, and then cooled to room temperature to obtain Al and LiH co-doped silicon negative electrode material; S5: Using the negative electrode material prepared in step S4 as the negative electrode, NCM811 / VGCF / Li 6 PS 5 Cl (mass ratio of 65:5:35) as the composite positive electrode, Li 6 PS 5 Cl is a solid electrolyte, and a solid-state lithium-ion battery with a laminated structure is obtained by cold pressing of powder.

[0044] Example 5 The Al and LiH co-doped silicon anode material was prepared and used in solid-state lithium-ion batteries by the following steps: S1: In an argon atmosphere, Si and LiAlH 4 The powder was preliminarily ground in a mortar to ensure that the two were evenly mixed to obtain Si / LiAlH 4 Mixed powder; S2: Si / LiAlH 4 The mixed powder was placed in a stainless steel ball mill, sealed, and mixed by planetary high-energy ball milling in an argon atmosphere. The ball-to-material ratio was set to 100:1, and the revolution speed of the ball mill was set to 400 rpm. The ball milling was performed for 2 h to obtain Si / LiAlH 4 Mixing ball-milled powders; S3: Si / LiAlH 4 The mixed ball-milled powder was pressed into powder tablets under a pressure of 150 MPa to obtain Si / LiAlH 4 Mixing and tableting; S4: Si / LiAlH 4 The mixed pressed tablets are placed in a stainless steel tube, and the stainless steel tube is evacuated by means of a vacuum diaphragm valve to ensure that the vacuum degree of the environment in the tube is not less than 10 kPa during the subsequent heat treatment, and the temperature in the tube is raised to 190° C. After heat treatment at 190° C. for 3 hours, the temperature is raised to 200° C., and the heat treatment is continued at 200° C. for 5 hours, and then cooled to room temperature to obtain Al and LiH co-doped silicon negative electrode material; S5: Using the negative electrode material prepared in step S4 as the negative electrode, NCM811 / VGCF / Li 6 PS 5 Cl (mass ratio of 65:5:35) as the composite positive electrode, Li 6 PS 5 Cl is a solid electrolyte, and a solid-state lithium-ion battery with a laminated structure is obtained by cold pressing of powder.

[0045] Comparative Example 1 This comparative example uses pure silicon negative electrode material, NCM811 / VGCF / Li 6 PS5 Cl (mass ratio of 65:5:35) as the composite positive electrode, Li 6 PS 5 Cl is a solid electrolyte, and a solid-state lithium-ion battery with a laminated structure is obtained by cold pressing of powder.

[0046] Comparative Example 2 The Al and LiH co-doped silicon anode material was prepared and used in solid-state lithium-ion batteries by the following steps: S1: In an argon atmosphere, Si and LiAlH 4 The powder was preliminarily ground in a mortar to ensure that the two were evenly mixed to obtain Si / LiAlH 4 Mixed powder; S2: Si / LiAlH 4 The mixed powder was placed in a stainless steel ball mill, sealed, and mixed by planetary high-energy ball milling in an argon atmosphere. The ball-to-material ratio was set to 100:1, and the revolution speed of the ball mill was set to 400 rpm. The ball milling was performed for 2 h to obtain Si / LiAlH 4 Mixing ball-milled powders; S3: Si / LiAlH 4 The mixed ball-milled powder was pressed into powder tablets under a pressure of 150 MPa to obtain Si / LiAlH 4 Mixing and tableting; S4: Si / LiAlH 4 The mixed pressed tablets are placed in a stainless steel tube, and the stainless steel tube is evacuated with the help of a vacuum diaphragm valve to ensure that the vacuum degree of the environment in the tube is not less than 10 kPa during the subsequent heat treatment. The temperature in the tube is raised to 180° C., and after heat treatment at 180° C. for 3 hours, the temperature is raised to 210° C., and the heat treatment is continued at 210° C. for 5 hours, and then cooled to room temperature to obtain Al and LiH co-doped silicon negative electrode material; S5: Using the negative electrode material prepared in step S4 as the negative electrode, NCM811 / VGCF / Li 6 PS 5 Cl (mass ratio of 65:5:35) as the composite positive electrode, Li 6 PS 5 Cl is a solid electrolyte, and a solid-state lithium-ion battery with a laminated structure is obtained by cold pressing of powder.

[0047] Comparative Example 3 The Al and LiH co-doped silicon anode material was prepared and used in solid-state lithium-ion batteries by the following steps: S1: In an argon atmosphere, Si and LiAlH 4The powder was preliminarily ground in a mortar to ensure that the two were evenly mixed to obtain Si / LiAlH 4 Mixed powder; S2: Si / LiAlH 4 The mixed powder was placed in a stainless steel ball mill, sealed, and mixed by planetary high-energy ball milling in an argon atmosphere. The ball-to-material ratio was set to 100:1, and the revolution speed of the ball mill was set to 400 rpm. The ball milling was performed for 2 h to obtain Si / LiAlH 4 Mixing ball-milled powders; S3: Si / LiAlH 4 The mixed ball-milled powder was pressed into powder tablets under a pressure of 150 MPa to obtain Si / LiAlH 4 Mixing and tableting; S4: Si / LiAlH 4 The mixed pressed tablets were placed in a stainless steel tube, and the stainless steel tube was evacuated with the help of a vacuum diaphragm valve to ensure that the vacuum degree of the environment in the tube was not less than 10 kPa during the subsequent heat treatment. The temperature in the tube was raised to 210° C., and heat treated at 210° C. for 8 h, and then cooled to room temperature to obtain Al and LiH co-doped silicon negative electrode material; S5: Using the negative electrode material prepared in step S4 as the negative electrode, NCM811 / VGCF / Li 6 PS 5 Cl (mass ratio of 65:5:35) as the composite positive electrode, Li 6 PS 5 Cl is a solid electrolyte, and a solid-state lithium-ion battery with a laminated structure is obtained by cold pressing of powder.

[0048] Comparative Example 4 The Al and LiH co-doped silicon anode material was prepared and used in solid-state lithium-ion batteries by the following steps: S1: In an argon atmosphere, Si and LiAlH 4 The powder was preliminarily ground in a mortar to ensure that the two were evenly mixed to obtain Si / LiAlH 4 Mixed powder; S2: Si / LiAlH 4 The mixed powder was placed in a stainless steel ball mill, sealed, and mixed by planetary high-energy ball milling in an argon atmosphere. The ball-to-material ratio was set to 100:1, and the revolution speed of the ball mill was set to 400 rpm. The ball milling was performed for 2 h to obtain Si / LiAlH 4 Mixing ball-milled powders; S3: Si / LiAlH 4 The mixed ball-milled powder was pressed into powder tablets under a pressure of 150 MPa to obtain Si / LiAlH4 Mixing and tableting; S4: Si / LiAlH 4 The mixed pressed tablets are placed in a stainless steel tube, and the stainless steel tube is evacuated by means of a vacuum diaphragm valve to ensure that the vacuum degree of the environment in the tube is not less than 10 kPa during the subsequent heat treatment, and the temperature in the tube is raised to 180° C. After heat treatment at 180° C. for 3 h, the temperature is raised to 450° C., and the heat treatment is continued at 450° C. for 5 h, and then cooled to room temperature to obtain Al and LiH co-doped silicon negative electrode material; S5: Using the negative electrode material prepared in step S4 as the negative electrode, NCM811 / VGCF / Li 6 PS 5 Cl mixture (mass ratio of 65:5:35) as the composite positive electrode, Li 6 PS 5 Cl is a solid electrolyte, and a solid-state lithium-ion battery with a laminated structure is obtained by cold pressing of powder.

[0049] Comparative Example 5 The Al and LiH co-doped silicon anode material was prepared and used in solid-state lithium-ion batteries by the following steps: S1: In an argon atmosphere, Si, Al and LiH powders with a molar ratio of 8:1:1 were preliminarily ground in a mortar to ensure that the three were evenly mixed to obtain Si / Al / LiH mixed powder; S2: Put the Si / Al / LiH mixed powder into a stainless steel ball mill, seal it, and mix it in an argon atmosphere using a planetary high-energy ball mill. The ball-to-material ratio is set to 100:1, and the revolution speed of the ball mill is set to 400 rpm. Ball milling is performed for 2 h to obtain Si / Al / LiH mixed ball milled powder; S3: Pressing the Si / Al / LiH mixed ball-milled powder into powder tablets at a pressure of 150 MPa to obtain Si / Al / LiH mixed tablets; S4: Put the Si / Al / LiH mixed pressed tablet into a stainless steel tube, evacuate the stainless steel tube with the help of a vacuum diaphragm valve to ensure that the vacuum degree of the environment in the tube is not less than 10 kPa during the subsequent heat treatment, raise the temperature in the tube to 180°C, heat treat at 180°C for 3 hours, then raise the temperature to 210°C, continue to heat treat at 210°C for 5 hours, and then cool to room temperature to obtain Al and LiH co-doped silicon negative electrode material; S5: Using the negative electrode material prepared in step S4 as the negative electrode, NCM811 / VGCF / Li 6 PS 5 Cl mixture (mass ratio of 65:5:35) as the composite positive electrode, Li 6 PS 5Cl is a solid electrolyte, and a solid-state lithium-ion battery with a laminated structure is obtained by cold pressing of powder.

[0050] Test Example 1: Al and LiH doping The negative electrode materials prepared in Example 1, Example 3 and Comparative Example 2 were tested for X-ray diffraction (XRD) patterns. Figure 2 .from Figure 2 It can be seen that when Si and LiAlH 4 When the molar ratio of Si and LiAlH is 2:1, the XRD spectrum shows obvious characteristic peaks of Al and LiH (due to the similarity of crystal structure, the characteristic peaks of Al and LiH basically coincide). 4 When the molar ratio is 8:1 and 18:1, due to the low content of Al and LiH and small grains, the detection limit of the XRD spectrum is not reached, so no obvious Al and LiH characteristic peaks are shown.

[0051] Test Example 2: Battery Performance The battery prepared in each embodiment and comparative example was subjected to a cycle performance test under the following test conditions: temperature 60°C, charge and discharge current 0.1C, pressure 50MPa. The measured first discharge specific capacity, first coulomb efficiency and capacity retention rate after 20 cycles are shown in Table 1; 4 The change of discharge capacity from the 1st to the 20th cycle is shown in Figure 1 .

[0052] Table 1 Battery performance test results

[0053] From Table 1 and Figure 1 It can be seen that: (1) The test results of Examples 1 to 5 and Comparative Example 1 show that, compared with pure silicon negative electrode materials, the method of the present invention can effectively improve the capacity, initial coulombic efficiency and cycle stability of the battery after introducing metal aluminum and lithium hydride doping therein. The reason for this is that: the method of the present invention can generate nano-sized metal aluminum and lithium hydride with high dispersion uniformity in situ, wherein metal aluminum has a high reversibility of alloying / de-alloying reaction, and lithium hydride with the above characteristics can generate an electric field effect with the lithium aluminum alloy and lithium silicon alloy formed during the battery charging process, promote the lithium ion transmission inside the negative electrode, and balance the electric field on the surface of the alloy material, thereby avoiding the growth of lithium dendrites induced by the local potential on the surface of the material.

[0054] (2) The test results of Examples 1 to 3 and Comparative Examples 1 to 2 show that in the process of preparing negative electrode materials, when Si and LiAlH 4When the molar ratio of LiAlH is 2-8:1, the capacity, first coulomb efficiency and cycle stability of the battery can be effectively improved compared with pure silicon negative electrode materials. 4 When the amount of silicon used is too small (Comparative Example 2), the capacity and cycle stability of the battery are reduced compared with pure silicon negative electrode materials.

[0055] (3) The test results of Example 1 and Comparative Example 3 show that compared with the one-step vacuum heat treatment method, LiAlH 4 As for decomposition into LiH and Al, the two-step vacuum heat treatment method of the present invention can improve the cycle stability of the battery. The reason for this is that when a one-step vacuum heat treatment method is used, the size of the generated lithium hydride is larger and the dispersion uniformity is poor, which will increase the local potential difference at each point on the surface of the alloy material, leading to the accelerated growth of lithium dendrites. For the same reason, in Comparative Example 5, LiH and Al are directly used to form doping in the silicon negative electrode material, and the cycle stability of the battery produced is lower than that of Example 1.

[0056] (4) The test results of Example 1 and Comparative Example 4 show that in the preparation process of Al and LiH co-doped silicon negative electrode materials, when the temperature of vacuum heat treatment is too high, the cycle stability of the battery will decrease. The reason is that when the temperature of vacuum heat treatment is too high, LiH will decompose, making it difficult to utilize the electric field effect between lithium hydride and lithium aluminum alloy and lithium silicon alloy to better promote the lithium ion transmission inside the negative electrode and balance the electric field on the surface of the alloy material, so the effect of improving the cycle stability of the battery is poor.

[0057] Test Example 3: Electronic conductivity of negative electrode materials The negative materials prepared in Example 1 and Comparative Example 1 were taken for electronic conductivity testing under the following testing conditions: temperature was 25°C and voltage was 10 mV. The measured current-time curve is shown in Figure 4 .from Figure 4 It can be seen that compared with pure silicon negative electrode materials, the electronic conductivity of silicon negative electrode materials can be effectively improved after doping with metal aluminum and lithium hydride using the method of the present invention.

[0058] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.

[0059] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing an Al and LiH co-doped silicon negative electrode material, characterized in that: The method comprises the following steps: after powder pressing Si and LiAlH4, vacuum heat treatment is performed at 160-190°C for 3-6 hours, and then vacuum heat treatment is performed at 200-300°C for 2-5 hours to obtain Al and LiH co-doped silicon negative electrode material.

2. The preparation method according to claim 1, characterized in that: The molar ratio of Si to LiAlH4 is 2-8:

1.

3. The preparation method according to claim 1, characterized in that: During the vacuum heat treatment at 160-190° C. and the vacuum heat treatment at 200-300° C., the vacuum degree is not less than 10 kPa.

4. The preparation method according to claim 1, characterized in that: Before powder tableting, Si and LiAlH4 were mixed and high-energy ball milled.

5. The preparation method according to claim 4, characterized in that: The mixing and high-energy ball milling processes are carried out in an inert atmosphere.

6. The preparation method according to claim 4, characterized in that: The high energy ball milling method is planetary ball milling.

7. The preparation method according to claim 4 or 6, characterized in that: During the high-energy ball milling process, the ball-to-material ratio is 60-120:1, the revolution speed is 200-500 rpm, and the time is 1-5 hours.

8. The preparation method according to claim 1, characterized in that: During the powder tableting process, the pressure is 100-300 MPa.

9. An Al and LiH co-doped silicon negative electrode material prepared by the preparation method according to any one of claims 1 to 8.

10. The use of the Al and LiH co-doped silicon negative electrode material in a lithium ion battery according to claim 9, characterized in that: The lithium-ion battery comprises a negative electrode; the negative electrode adopts the Al and LiH co-doped silicon negative electrode material.

Citation Information

Patent Citations

  • Anode active material for battery and preparation method thereof

    CN111180692A

  • Preparation method of metal-doped silicon-based negative electrode material, negative electrode material and secondary battery

    CN115663153A

  • Simple pre-lithium metal doped silicon-oxygen-carbon negative electrode material and preparation method thereof

    CN116093300A

  • Short-range ordered noble metal catalyst as well as preparation method and application thereof

    CN117822034A

  • Method for forming polycrystalline silicon film and composition therefor

    JP2003054931A